PERANAN AUDIT OPRASIONAL DALAM MENINGKATKAN EFEKTIVITAS DAN EFISIENSI SYSTEM PENJUALAN PADA PERUSAHAAN PT. ANDALAN FINANCE - Rohmatin, Rohmatin; Widiastoeti, Hendy (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTBased on the test results and a discussion of the operational audit role in improving the effectiveness and efficiency of the sales system in PT. Mainstay of Finance, the researchers can summarize that the effectiveness and efficiency of sales amounted to 96.00%, the value can answer the problem formulation and may imply that the sales activity in the mainstay Finance "Highly effective" although there are some findings that should be corrected. Thus the results of this study can be answered from the results of audits of product marketing. Results of audits found several weaknesses which should be a concern of management in the future. The downside to this is are No system better dokomentasi the mainstay penjulan finance and No atauran strong employee. The overall weakness of the case, then given the recommendation as a corrective or remedial measures that can be taken to improve the management of these weaknesses. Recommendation: The Company determines the SOP (standard Operating Procedure) for each of the divisions that exist in the branch in writing in SK. The company must have a good sales documentation and easily understood by all divisions and have a good document security. The Company regularly obliged to make improvements to the program of sales over a couple of problems that often terjadaji. The company made the SOP regarding employees' contained in the decree recruitment written and clear. Key: audits, SOP, system, sales